Revisiting the management of heart failure with reduced ejection fraction - Majumder, Abdullah Al Shafi (Bangladesh Journal of Medicine, 2024)
Management of HFrEF include: life style changes : diet. weight management, exercise , pharmacotherapy : “ Fantastic four - RAAS inhibitors, Beta-blockers, SGLT 2 inhibitors, MRAs”; diuretics – symptom relief; Ivabridine ; Digoxin in selected patients; Vericiguat, Omicamtiv, Device therapy : CRT; ICD, Interventional : MV repair, Coronary angioplasty and Surgical – CABG; Repair or replacement of diseased valves, LV aneurysmectomy etc. Adjunct therapy in HFrEF are correction of iron deficiency: Inj ferric carboxymaltose, management of thyroid dysfunction and management of any associated risk factors. Periodic follow-up : clinical assessment, LV dimension & systolic function by echocardiography; NT-pro BNP level ; Renal function & S electrolytes. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 135